Sistem Presensi dan Sertifikasi Elektronik Memanfaatkan QR Code Menggunakan Algoritma AES - Harfidz Alif Alfatihah; Iskandar Fitri; Andrianingstih Andrianingsih (LPPM STIKI MALANG, 2021)
Presence is an important element in carrying out teaching and learning activities in lectures, student attendance is evidence that the student has attended the seminar. Attendance is also an element of student assessment that has been determined by the university. Cheating in attendance that occurred during seminar activities caused injustice among students, so that many students objected to being absent and were then given the same seminar certificate by the lecturer. Certificates are evidence obtained from students attending seminars, as technology develops, E-certificates appear. The method applied in the development of the Electronic Presence and Certification System Using the web-based AES Algorithm using QR code scan technology is a prototype method. Taking this method is to produce applications that suit user needs. With QR Code technology, it will facilitate the process of attendance and checking of e-certificates automatically and computerized and will minimize student cheating in the process of attendance and ownership of e-certificates, because the QR Code will change every meeting. The resulting system has a QR Code scanning feature from existing applications and will be recorded in the database on the server.